2D Zn‐Hexamine Coordination Frameworks and Their Derived N‐Rich Porous Carbon Nanosheets for Ultrafast Sodium Storage. Issue 22 (23rd May 2018) - Liu, Sitong; Zhou, Jisheng; Song, Huaihe
Abstract: Metal‐organic coordination frameworks have been widely used as efficient precursors for the preparation of functional carbon‐based materials with various nanostructures. However, to date, the design of 2D carbon nanostructures from single coordination frameworks remains a great challenge. Herein, an efficient strategy for the fabrication of N‐rich porous carbon nanosheets from 2D Zn‐hexamine coordination framework nanosheets is developed. Remarkably, the N‐doping level of carbon nanosheets can attain 16.54 at%. In addition, the thickness of the carbon nanosheets can effectively be tuned by simply adjusting the molar ratio of the starting materials. As a proof‐of‐concept application, the as‐prepared carbon nanosheets as an anode material for sodium‐ion batteries exhibit an ultrafast sodium storage capability of 194 mAh g −1 even at 10 A g −1 . As far as it is known, such a high‐rate capability has been rarely achieved in previous studies on carbonaceous anode materials for Na‐ion storage. Moreover, this approach is readily controllable and could be extended to prepare a series of 2D N‐doped carbon‐based nanomaterials on a large scale. Abstract : 2D zinc‐hexamine coordination frameworks are facilely designed for the first time to derive N‐rich porous carbon nanosheets with the high N‐doping level of 16.54 at% and controlled thickness. As a proof‐of‐concept application, the carbon nanosheets exhibit an ultrafast sodium storage capability of 194 mAh g −1 at 10 A g −1 and ultralong cyclic life.